Effectiveness of a modified 6-Fr endoscopic nasobiliary drainage catheter for patients with preoperative perihilar cholangiocarcinoma - Kawashima, Hiroki; Hirooka, Yoshiki; Ohno, Eizaburo; Ishikawa, Takuya; Miyahara, Ryoji; Watanabe, Osamu; Hayashi, Kazuhiko; Ishigami, Masatoshi; Hashimoto, Senju; Ebata, Tomoki; Nagino, Masato; Goto, Hidemi (Endoscopy International Open, 2018)
Background and study aims To decrease complications associated with preoperative endoscopic nasobiliary drainage (ENBD) for perihilar cholangiocarcinoma patients, we developed a modified 6-Fr ENBD catheter with multiple side holes (m-ENBD). The aim of this retrospective study was to compare the m-ENBD catheter with a conventional 7-Fr ENBD catheter (c-ENBD). Patients and methods This study involved 371 patients with suspected perihilar cholangiocarcinoma who underwent ENBD using a c-ENBD catheter or an m-ENBD catheter. The effectiveness of each catheter and the incidence of complications were evaluated. Univariate and multivariate analyses followed by propensity score matching were performed. Results In 145 patients with total bilirubin levels ≥ 2.0 mg/dL prior to drainage, these levels decreased to < 2.0 mg/dL after ENBD in 81.1 % of the c-ENBD patients and in 74.0 % of the m-ENBD patients (P = 0.325). Post-ENBD cholangitis occurred in 24.9 % of the c-ENBD patients and in 12.4 % of the m-ENBD patients (P = 0.006). After propensity score matching, the rate of post-ENBD cholangitis (P = 0.007) and the number of patients requiring subsequent or additional drainage (P = 0.030) were significantly lower in the m-ENBD group.Conclusion The modified 6-Fr ENBD catheter was associated with a lower incidence of post-ENBD cholangitis than the conventional 7-Fr ENBD catheter, and the incidence of subsequent or additional drainage procedures was also decreased.